National Service for Health : the Labour Party's post-war policy (London : Labour Party)
1943-04 1943 1940s 24 pages (3) POST-NATAL SERVICES. As far as possible all patients should be seen after childbirth by the same staff as were responsible during the ante-natal care and at the birth. At least one full examination of the patient should be made, and advice should be available at the Health Centre. It is important that further home help should be provided when required, and that there should be convalescent homes to which mothers can be sent after childbirth for periods of rest if necessary. Tuberculosis Among the diseases connected with poverty, none is more deadly than tuberculosis. Wherever we find poverty, poor food, over-crowding, over-work, lack of good air, there we find a high tuberculosis rate. Between the wars, the death-rate from tuberculosis in England and Wales was reduced by more than half, but even so the deaths in 1938 amounted to 26,000. With the outbreak of the present war this improvement was sharply reversed, especially in Scotland. The Government have taken one important step to deal with this, by providing for cheap and rapid X-ray examination, so as to identify the disease while it is still amenable to treatment. But this provision for improved diagnosis will not have its proper effect unless certain other conditions are satisfied. There must be adequate subsistence allowances for a patient's family during his or her absence ; otherwise the patient will be tempted to postpone until too late the opportunity — which is also a social duty — of undergoing the treatment even at a time when he may still be feeling well. The same applies to the provision of home help. There must be adequate staff and accommodation in hospitals and sanatoria, so that patients are not kept waiting. Further, when the patient is convalescent, there should be provision for "rehabilitation," with suitable work, both for infectious and non-infectious cases. In all these respects, new developments are needed, as part of the State's comprehensive Medical Service. Finance of the Scheme How should the finance of a comprehensive National Medical Service be organised? The Labour Party considers that the necessary expenditure should be drawn: (a) Partly from national taxation, expended directly by the Ministry of Health (e.g., for the National Health inspectorate); (b) Partly from national taxation, allocated by the Ministry of Health to Regional Authorities in the form of percentage grants ; (c) Partly from rates payable to Regional Authorities. The Ministry of Health should allocate to each Regional Authority a grant amounting to a percentage of its approved health expenditure; the object being (a) To provide a Health Service which is preventive, comprehensive, open to all, and efficient as judged by national standards ; (b) To even out the present inequalities of standard between different areas. The Ministry of Health should be empowered to exercise "powers of default" in the event of continued failure by a Regional Authority to carry out its functions as a Health Authority in accordance with the principles and standards nationally laid down. 21 36/H24/40